Observations of the anomalous third Schumann resonance peak during October 21 to 25, 2004 at Modra Observatory and a possible explanation - KOSTECKÝ, Pavel; ONDRÁŠKOVÁ, Adriena; ŠEVČÍK, Sebastián; ROSENBERG, Ladislav; KOHÚT, Igor (Contributions to Geophysics and Geodesy, 2021)
At the Astronomical and Geophysical Observatory of FMFI UK at Modra, the permanent monitoring of Schumann resonance (SchR) spectra has been performed for more than three years (in electric field component – the SchR magnetic field component spectra have been measured – up to now – only intermittently for a shorter time). During second half of October 2004, several cases of anomalously high third SchR mode amplitude were observed. Because the man-made artifacts as a cause can be (with high probability) excluded, we seek for the possible natural explanation. Two explanations appear to be physically plausible: the occurrence of multiple return strokes (MRS) or the very special geometrical source-receiver relations. We propose that the dynamical behavior of short-interval spectra can distinguish between them